Socio-economic Impact of Contract Farming - Arnab Biswas, Baldeo Singh,Premlata Singh (Indian Journal of Extension Education, 2022)
The study was conducted in Burdwan district of West Bengal with randomly selected 50 potato contract and 50 non contract potato growers as respondents to assess the impact of contract farming. From the study it was found that contract farming helps the farmers to diversify their farming. After engaging in contract farming farmers cultivated more number of crops per season and they also cultivated more number of potato varieties. The acreage under vegetable crop was also increased more than 165 per cent than before. Significant increase was found after introduction of contract farming in case of employment opportunity (56.61%) and acreage under potato crop (57.54%). The net benefit from potato was 33.83 per cent higher in case of contract farmers than non contract farmers. In case of input utilization contract farmers used 128.94 per cent more seed per acre, 15.85 per cent more urea per acre than non contract farmers